Effectiveness of Transition Readiness Interventions by School-Based Occupational Therapy Personnel. (January 2020) - Pierce, Doris; Sakemiller, Lisa; Spence, Amy; LoBianco, Tony
Despite federal mandates to transition students with disabilities to successful adulthood, outcomes have been poor. Although areas of occupational therapy expertise, such as life and work skills, are effective in improving transition outcomes, occupational therapy personnel rarely provide transition services. The purpose of this study was to examine the effectiveness of occupational therapy transition readiness services for students with disabilities, 14 to 16 years of age, over two academic years of intervention. Forty-two students and 14 occupational therapy personnel from 10 school districts participated. Assessments were provided to transition teams. Peer groups explored work and life skills and completed long-term student-led projects. Pre–post scores of functional behavior were analyzed using a proportional change index. Students receiving occupational therapy transition readiness services demonstrated statistically significant gains. Occupational therapy holds potential to increase the functional readiness of students with disabilities for transition to a successful and productive adult life.